Infective endocarditis associated with Bartonella henselae: A case series. (2018) - Nakasu, Akio; Ishimine, Tohru; Yasumoto, Hiroshi; Tengan, Toshiho; Mototake, Hidemistu
Abstract: Organisms in the genus Bartonella are cause of blood culture-negative endocarditis. Bartonella infective endocarditis is being increasingly reported worldwide; however, reports from Japan are limited. Here, we report five cases of infective endocarditis associated with Bartonella henselae . All patients had a history of contact with cats or fleas; this information helped achieve an appropriate diagnosis.